Examining Differences in Work-life Balance of Early Career and Seasoned Academicians - Kavi, Sanket; Verma, Twinkle (Leading the Charge: A Guide to Management, Entrepreneurship and Technology in the Dynamic Business Landscape Edition 1, 2025)
This research paper investigates the dynamics of work-life balance and stress management within the faculty community of universities in Dehradun, with a specific focus on age-related factors. The study will categorize faculty members into Early Career Academicians and Seasoned Academicians groups to discern variations in their experiences and coping mechanisms. The primary aim is to analyze how the challenges and coping mechanisms vary between the younger and older age groups within the academic community. The research adopts a descriptive study design, employing a mixed-methods approach to gather comprehensive insights. Quantitative surveys have been distributed among several universities of Dehradun to collect demographic information, work-related data, and stress levels. Qualitative surveys have been conducted as semi-structured interviews to delve deeper into the subjective experiences, exploring the impact of age on work-related stress and coping mechanisms. The findings of the study revealed the phenomenon of stress among faculty members in academia, with a specific focus on understanding why Early Career Academicians may experience higher stress levels compared to their established counterparts. Examining various factors, including career establishment, job insecurity, teaching challenges, financial pressures, organizational adaptation, and work-life balance struggles. The implications of elevated stress levels on individual well-being, job satisfaction, and overall efficiency, this research seeks to contribute to a nuanced understanding of stress dynamics in academic settings. The findings may inform targeted interventions, support mechanisms, and institutional policies aimed at alleviating stress among younger faculty members and fostering a healthier work environment within academia.